ANALYSIS OF THE EFFECTIVENESS OF PROJECT-BASED LEARNING ON STUDENTS’ CREATIVE THINKING SKILLS - Solehah, Firdatus; Umamah, Chairatul; Budiono, Agus (EduFisika: Jurnal Pendidikan Fisika, 2025)
The research aims to analyze the efficiency of the Project-Based Learning (PjBL) model, focusing on the development of students’ creativity skills on the topic of heat. Creativity is one of the most essential skills in the 21st century. A quasi-experimental method was employed in this study, using a Non-Equivalent Control Group Design. The population of this research consisted of Grade XI senior high school students. The study used an essay test comprising four questions, developed around aspects of creativity, including fluency, flexibility, originality, and elaboration. The research findings show that implementing the PjBL model in the experimental class significantly increases creative thinking skills. The hypothesis test results were reinforced by a Sig. (2-tailed) value of 0.000 < 0.05, indicating that H0 was rejected and H1 was accepted. H1 was accepted because the experimental group applied the project-based learning model. These findings demonstrate that the project-based learning model is effective in enhancing creativity skills. The control group obtained an N-Gain score of 0.33, classified as low, while the experimental group achieved an N-Gain score of 0.56, classified as medium. In addition, the obtained effect size of 1.9683 indicated a very large effect size. Thus, the PjBL model is effective for use in physics learning activities aimed at optimizing students’ creative thinking skills.